1989
DOI: 10.1007/bf02442162
|View full text |Cite
|
Sign up to set email alerts
|

Cycling device powered by the electrically stimulated muscles of paraplegics

Abstract: The paper describes a device (Paracycle), that uses functional neuromuscular stimulation to exercise subjects, explore FNS technology and provide paraplegics with locomotion. The Paracycle is a four-wheeled cycling vehicle that may be used as a stationary exercise device or for locomotion. It incorporates a fully adjustable seat and an electric motor to assist or retard the cycling motion, as well as speed and direction controls. Furthermore, it has braces to fasten the feet to the pedals and to stabilise the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…While most previous studies have utilised stationary FES-cycling ergometers, a number of mobile devices have also been proposed [5,6,7,8,9], raising the possibility that FES-cycling might become a recreational activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most previous studies have utilised stationary FES-cycling ergometers, a number of mobile devices have also been proposed [5,6,7,8,9], raising the possibility that FES-cycling might become a recreational activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have analysed electromyographic (EMG) data from normal subjects during volitional cycling to identify muscle timing characteristics [17,18,19,6,20], and have attempted to use the results to design activation ranges for SCI subjects performing FES-cycling on the same ergometer device. Two of these studies, [6,20], found that the activation patterns obtained during normal, volitional cycling had to be manually adjusted in order to achieve smooth cycling motion with paraplegic subjects. Petrofsky's studies [17,18,19] each reported measurement of EMG activation patterns from four normal subjects, and the apparently successful use of these to set the timing and stimulation intensity variables for paraplegic cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, very little data reporting testing of these mobile devices with paraplegic subjects, or usage outside of laboratory conditions, have been published, and it is, therefore, difficult to assess their utility. We note that the systems described by Pons et al [3] and Gföhler et al [4] both included an auxiliary electric motor. In both cases, the motor is manually controlled in a feedforward manner.…”
Section: Mobile Recreational Cyclingmentioning
confidence: 93%
“…Several groups have described mobile FES cycles [1], [3], [4], [13]. Unfortunately, very little data reporting testing of these mobile devices with paraplegic subjects, or usage outside of laboratory conditions, have been published, and it is, therefore, difficult to assess their utility.…”
Section: Mobile Recreational Cyclingmentioning
confidence: 99%
See 1 more Smart Citation